PERBEDAAN KELUHAN MUSKULOSKELETAL SEBELUM DAN SESUDAH PEMBERIAN PERLAKUAN LATIHAN PEREGANGAN PADA PETUGAS KESEHATAN GIGI DI PUSKESMAS KECAMATAN MEDAN AREA TAHUN 2012 - Sri Yusnani (Lingkungan dan Kesehatan Kerja, 2012)
The Difference of Musculoskeletal Disorder Before and After Treatment Stretching Exercises on Dental Health in Medan Area District Health Center in 2012.This research was conducted to determine differences in musculoskeletal disorders before and after treatment stretching exercises on dental health in Medan Area District Health Center in 2012. The study was designed praeksperimental ie; one group pre test and post test design in order to determine differences in musculoskeletal disorders before and after treatment stretching exercises on dental health in Medan Area District Health Center in 2012. Samples based on total sampling as many as 8 people. Musculoskeletal disorders measured by nordic body map. From the measurement results it can be seen that musculoskeletal disorders after stretching the category of pain and not felt of respondents by 8 (100%), with a bit of a pain that most categories perceived by respondents were in the upper neck, lower neck, 7 (87.5%). Based on the Wilcoxon test is known that musculoskeletal disorders before and after the stretching exercises on the upper neck, lower neck, left shoulder, right upper arm, waist, left forearm, right forearm and right wrist has a value of p <0.05 (have difference musculoskeletal disorders stretching before and after exercise). It is recommended that health care workers perform stretching exercises teeth after 4 hours of work by targeting specific locations that could potentially lead to pain and imbalance. Keywords: workers, musculoskeletal disorders, Stretching Exercises